Fermentation-Mediated Modulation of Nutraceutically Relevant Polyphenolic Compounds and Antioxidant Capacity of Red Spinach (Amaranthus tricolor L.) Leaf Extract - Nur Amelia; Yovi Pranata; Arif Setiawansyah; Mauritz Pandapotan Marpaung; Fika Minata Wathan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Fermentation has emerged as a promising biotechnological approach to enhance the nutraceutical quality of plant-based materials through targeted modulation of bioactive compounds. This study investigated the effects of aerobic and anaerobic fermentation on total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity of red spinach (Amaranthus tricolor L.) leaf extracts. Aerobic fermentation markedly enhanced the phytochemical profile, yielding a 1.87-fold increase in TPC (121.28 mg GAE/g extract) and a 1.66-fold increase in TFC (897.82 mg QE/g extract) compared with fresh leaves. These compositional improvements translated into superior functional activity, as evidenced by the lowest IC50 value (56.07 mg/L) and the highest antioxidant activity index (AAI = 0.713). In contrast, anaerobic fermentation provided limited phenolic enrichment and resulted in substantial flavonoid degradation, leading to inferior antioxidant performance. Strong correlations between polyphenolic contents and antioxidant parameters confirmed that phenolics and flavonoids are key contributors to radical scavenging activity. Overall, the findings demonstrate that aerobic fermentation is an effective, low-cost strategy to improve the nutraceutical value and antioxidant capacity of red spinach leaf extracts, highlighting its potential application in the development of functional foods and nutraceutical ingredients.